The impact of war on the health system of the Tigray region in Ethiopia: an assessment. Issue 11 (23rd November 2021) - Gesesew, Hailay; Berhane, Kiros; Siraj, Elias S; Siraj, Dawd; Gebregziabher, Mulugeta; Gebre, Yemane Gebremariam; Gebreslassie, Samuel Aregay; Amdes, Fasika; Tesema, Azeb Gebresilassie; Siraj, Amir; Aregawi, Maru; Gezahegn, Selome; et al.
Abstract : The war in Tigray region of Ethiopia that started in November 2020 and is still ongoing has brought enormous damage to the health system. This analysis provides an assessment of the health system before and during the war. Evidence of damage was compiled from November 2020 to June 2021 from various reports by the interim government of Tigray, and also by international non-governmental organisations. Comparison was made with data from the prewar calendar year. Six months into the war, only 30% of hospitals, 17% of health centres, 11.5% of ambulances and none of the 712 health posts were functional. As of June 2021, the population in need of emergency food assistance in Tigray increased from less than one million to over 5.2 million. While the prewar performance of antenatal care, supervised delivery, postnatal care and children vaccination was 64%, 73%, 63% and 73%, respectively, but none of the services were likely to be delivered in the first 90 days of the war. A conservative estimate places the number of girls and women raped in the first 5 months of the war to be 10 000. These data indicate a widespread destruction of livelihoods and a collapse of the healthcare system. The use of hunger and rape as a weapon of war and the targeting of healthcare facilities are key components of the war. To avert worsening conditions, an immediate intervention is needed to deliver food and supplies and rehabilitate the healthcare delivery system and infrastructure.